A Comparative Study of the University Entrance Examination in China and the USA: From the Perspective of the Social Reproduction Based on SAT and Gaokao - Liu , Yuqiao (Research Highlights in Language, Literature and Education Vol. 7, 2023)
Gaokao and SAT promote the social reproduction in different ways during the university entrance examination. In China and the United States, Gaokao and SAT are university entrance exams that seem to operate in a similar way, but are rife with disparities. Gaokao and SAT not only represent two different educational systems, they also represent two forms of social reproduction. In comparison with the SAT, Gaokao is comparatively fair since the social capitalism does not completely permeate in China's educational system. The aspect of tuition can also be fully acknowledged. In the United Stated, however, SAT has been completely inundated by the American capital. This is because university admissions in the United States are not based on a single test which takes into account the entire profile of a student.as they believe that developing comprehensive qualities requires considerable time and effort, which must be accompanied by financial resources. As a result, the universities in the United States prefer all-rounded students, usually come from high social level families.